Translational Science: A Road Map for the Science of Reading. (9th September 2020) - Solari, Emily J.; Terry, Nicole Patton; Gaab, Nadine; Hogan, Tiffany P.; Nelson, Nancy J.; Pentimonti, Jill M.; Petscher, Yaacov; Sayko, Sarah
ABSTRACT: Despite scientific advances that have informed our understanding of reading acquisition and development, a profound gap exists between empirical findings and the implementation of evidence‐based practices in the assessment and instruction of reading in school settings. The debate regarding the practical implications of the science of reading (SOR) and its implementation in authentic school settings is palpable. As researchers, practitioners, policymakers, parents, and other educational stakeholders engage in this latest version of the debate on how best to teach young learners to read, a familiar, almost cyclical, narrative has emerged. As an interdisciplinary group of researchers who study diverse facets of reading development, assessment, and instruction, it is troubling how little the current and past debates have focused on processes that could ensure that the instructional experience students receive in classrooms is informed by existing science. Specifically, the authors contend that the persistent gap between the SOR and its school‐based implementation exists because the field has yet to invest in the appropriate methodologies and processes to develop an effective model of translational science. The authors argue not only that much can be learned from previous iterations of this debate but also that advances in translational science provide a framework for how to address the SOR debate differently and more productively in the current climate. Thus, the authors propose a road map for translational science for the SOR, acknowledging the breadth of work done in translational science in other fields and recognizing and describing the added complexities in the emerging field of translational science in educational settings.